Cytokines, reverse genetics and anti-cytokine therapy - M. S. Drutskaya (Bûlleten' Sibirskoj Mediciny, 2019)
Cytokines comprise the molecular language of communication between the cells, which is needed to maintain the homeostatic functions of the body (including the immune system) and mediate various diseases. Many aspects of inflammation, autoimmune diseases and neoplasia are associated with cytokine signaling through specific receptors. The establishment of new physiological functions of “old” cytokines and understanding the molecular and cellular mechanisms of their involvement in disease pathogenesis, as well as the search for new therapeutic targets and development of innovative approaches to anti-cytokine therapy, present a fundamental problem. When assessing the tremendous success of anti-cytokine therapy in treatment of certain autoimmune diseases, we should not forget that (a) this treatment does not eliminate the causes of the disease:autoreactive T-cell clones; and that (b) less than half of the patients respond to this therapy; and that (c) anti-cytokine therapy has serious side effects.